Minimally invasive saphenous vein harvesting: effects on endothelial and smooth muscle function. - Black, E; Guzik, T; West, N; Campbell, K; Pillai, R; Ratnatunga, C; Channon, K (2001)
BACKGROUND: The long saphenous vein remains the commonest conduit used in coronary artery bypass grafting procedures. Surgical trauma during vein harvesting can cause endothelial and smooth muscle injury that has important implications for vein graft longevity. Minimally invasive vein harvesting is advocated to reduce wound morbidity. However, the functional consequences of increased handling and traction, with potentially detrimental effects, remain unknown. METHODS: Forty patients were prospectively randomized into either a minimally invasive (minimal) or traditional (open) saphenous vein harvest group. Smooth muscle contractile function was assessed by responses to potassium chloride and phenylephrine. Endothelial cell function was assessed by responses to serial escalations in concentration of acetylcholine, bradykinin, calcium ionophore, sodium nitroprusside, and N-nitro-L-arginine using isometric tension studies. RESULTS: Harvest times were similar for both groups. The total incision length in the minimal group was significantly shorter than in the open group. There were no differences in smooth muscle contractions to either receptor-independent or receptor-mediated agonists between the two groups. Similarly, vasorelaxation in response to both endothelium-dependent and endothelium-independent agonists were similar in both groups. CONCLUSIONS: Minimally invasive saphenous vein harvesting is associated with similar medial smooth muscle and endothelial function as open harvesting. These findings suggest that minimally invasive harvesting techniques can be used without major detrimental effects on vascular integrity.